Melchior Inchofer, Giordano Bruno, and the soul of the world. - Martinez, Alberto A. (Annals of Science)
Following Galileo's trial of 1633, the Jesuit theologian Melchior Inchofer, author of the most negative reports used by the Roman Inquisition against Galileo, repudiated the Copernicans for the 'heresy' of the soul of the world (anima mundi), in an unpublished manuscript. I show that Inchofer's arguments applied far more to the beliefs of Giordano Bruno than to those of Galileo. Since antiquity, various Christian authorities had repudiated several beliefs about the anima mundi as 'heretical', hence I review their critiques against Pythagoras, Origen, and Peter Abelard, for allegedly asserting animistic beliefs about the Earth, or a universal spirit, or that souls move the heavenly bodies. Still, in the Renaissance such beliefs were defended by several advocates of Copernicus, including Bruno, William Gilbert, Johannes Kepler, and Philips Lansbergen, who all claimed that Earth moves because it has a soul. By comparing Inchofer's works and some of the Roman Inquisition's earlier censures against Bruno, I argue that the repudiation by many prominent Catholic theologians of pagan notions of the anima mundi as heretical contributed partly to the later theological opposition to the Copernicans.